Strategic business rules for business process intelligence : An oracle prototype - Kaula, Rajeev (Journal of Advanced Computer Science & Technology, 2014)
Business process intelligence aims to provide timely information to improve business process effectiveness and align it with business objectives in order to compete successfully in the marketplace. Generally such information not only improves an organizations ability to accomplish business objectives, but may also lead to the identification of information that could facilitate competitive advantage. This paper outlines an approach to develop an information flow model that involves the specification of activity dimensions during business process modeling to develop dimensional models to identify process metrics through strategic business rules that aligns a business process with business objectives. The paper illustrates the concepts through a marketing business process Lead to forecast prototype which is implemented in Oracle’s PL/SQL language.   Keywords: Business Intelligence, Business Process, Business Process Metrics, Business Process Intelligence, Business Rules.